Impact of Postbiotic Produced from Lactobacillus rhamnosus NCDC 298 as a Replacement for Antibiotics on the Growth Performance, Gut Health and Immune Response in Broiler Chickens - Soren, Stephen; Ghosh, Ranjita; Mandal, Guru Prasad; Mandal, Surojit; Samanta, Indranil (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during the month of June–July 2025 at the Department of Animal Nutrition, WBUAFS, Kolkata, West Bengal, to study the effect of postbiotics on broiler chicken performance. This study aimed to assess the impact of dietary supplementation with a postbiotic (inactivated Lactobacillus rhamnosus NCDC 298) on the performance of broiler chickens. A total of 162 day-old broiler chicks were randomly assigned to three dietary groups: 1) basal diet (CON), 2) basal diet with antibiotic (Bacitracin methylene disalicylate-BMD) at 500 gton-1 feed (AGP), and 3) basal diet with postbiotic at 1 ml/bird in drinking water (POS). Body weight, feed intake, and feed conversion ratios (FCR) were monitored weekly for 42 days. Blood biochemistry and immune response were assessed ondays 28 and 35 of the trial. Carcass traits, gut microbiome, and gut morphology were evaluated at the end of the trial.The results showed that the postbiotic supplementation (POS) significantly improved FCR compared to the CON and AGP groups (p<0.05). Antibody titers for infectious bursal disease virus (IBDV) and Newcastle disease virus (NDV) did not differ significantly among the groups, except for a higher NDV titer on day 28 in the POS group compared to CON and AGP (p<0.05). Total E. coli counts were significantly lower in the POS group compared to CON and AGP (p<0.05), while total Salmonella counts were lower in the POS group compared to CON (p<0.05). In conclusion, postbiotic supplementation shows promise as an alternative to antimicrobials in broiler production.